EKSISTENSI DEWAN PERWAKILAN RAKYAT DAERAH PROVINSI RIAU TERHADAP PENGELOLAAN KEUANGAN DAERAH DALAM TINDAK LANJUT REKOMENDASI LAPORAN HASIL PEMERIKSAAN BADAN PEMERIKSA KEUANGAN - Putri, Athifa Syziya; Artina, Dessy; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Research related to the DPRD of Riau Province with follow-up recommendations on the results of the audit by the BPK is a study that focuses on the existence of the DPRD of Riau Province in overseeing the implementation of follow-up recommendations on the results of the audit by the BPK.The main issues and focus on which the research and preparation of this paper are based are assessing, knowing, and analyzing the role of the DPRD of Riau Province in carrying out its oversight function on the follow-up of recommendations on the audit results of the BPK to realize transparent regional financial governance within the Government Riau Province.This research is a sociological law because it describes legal problems in the implementation of follow-up recommendations on the audit results of the BPK. This research was conducted at the DPRD of Riau Province, the BPK Republic of Indonesia Representative of the Riau Province, and Regional Inspectorate of Riau Province. The population and sample in this study were members of Commission III and Commission IV of the DPRD of Riau Province, the Head of Riau Sub-Auditorate I BPK Republic of Indonesia Representatives of the Riau Province, and Inspector of the Regional Government of Riau Province. Sources of data in this study are primary data and secondary data, with data collection techniques through interviews and literature review.From the results of the study, it can be concluded that the existence of the DPRD of Riau Province on the follow-up to the audit results of the BPK is not in accordance with the Regulation of the Minister of Home Affairs of the Republic of Indonesia Number 13 of 2010 concerning Guidelines for Implementing the Oversight Function of the DPRD on the follow-up on the BPK results. Factors causing the DPRD of Riau Province to have difficulty encouraging officials who do not follow-up on recommendations on the audit results of the BPK are, among others due to employee mutations and a change in the organizational structure of work procedures. The application of the law to officials who do not carry out the follow-up recommendations for the audit results by the BPK is an administrative namely in the form of a written warning, while the criminal sanction has never been applied because there are no implementation instructions in the statutory regulations.Keywords: Excitence – Regional Finance – Follow-up